TETRALOGI FALLOT: ULASAN SINGKAT PENCITRAAN RADIOLOGIS - Laurensius Amedeo Sitindaon; Sri Indah Aruminingsih (CV. Jasa Sukses Abadi, 2023)
Tetralogy of Fallot is the most common cyanotic congenital heart disease. Tetralogy of Fallot has four classic cardiac anatomical abnormalities in the form of ventricular septal defect, pulmonary stenosis or right ventricular outflow tract obstruction, right ventricular hypertrophy, and overriding aorta. Each component has a varying degree of severity and influences the severity of its clinical manifestations. In addition to the four classic anatomic abnormalities, tetralogy of Fallot can also be accompanied by extracardiac abnormalities, some of which are related to the coronary and pulmonary arteries. The complexity of the anatomic abnormalities of this disease increases the need for an organized and combined imaging approach so as to optimize the diagnosis and optimal follow-up plan. Several diagnostic tools may be used, either alone or in combination, depending on the indication, patient age and clinical condition, local availability and expertise, cost of each device, and possible need for intervention. Chest X-ray serves as the initial modality in evaluating suspected congenital heart disease by reviewing heart size and great vessel abnormalities. Transthoracic echocardiography is the best diagnostic modality in diagnosing congenital heart disease including tetralogy of Fallot and intracardiac abnormalities but in some cases cannot evaluate extracardiac abnormalities. Computed tomography, magnetic resonance imaging, and angiography are imaging adjuncts in the evaluation of extra-cadiac abnormalities and may be adjuncts in pre- and postoperative evaluations. Each of these radiological imaging modalities has its own advantages and limitations in evaluating tetralogy of Fallot.